2020
DOI: 10.3390/jcm9020503
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hyponatremia on COPD Exacerbation Prognosis

Abstract: The most common electrolyte disorder among hospitalized patients, hyponatremia is a predictor of poor prognosis in various diseases. The aim of this study was to establish the prevalence of hyponatremia in patients admitted for acute exacerbation of chronic obstructive pulmonary disease (AECOPD), as well as its association with poor clinical progress. Prospective observational study carried out from 1 October 2016 to 1 October 2018 in the following hospitals: Salnés in Vilagarcía de Arousa, Arquitecto Marcide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 54 publications
4
21
1
Order By: Relevance
“…However, higher frequency of anemia, pleural effusion, higher values of leukocytes, and CRP have been observed in patients with hyponatremia. 13 In line with the literature, the present study also found similar values regarding age, gender, LTOT, and NIV usage in patients with normonatremia and hyponatremia. CCI scores, leucocytes, neutrophils, AST, and CRP values were higher in hyponatremia whereas hemoglobin and lymphocytes were lower.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, higher frequency of anemia, pleural effusion, higher values of leukocytes, and CRP have been observed in patients with hyponatremia. 13 In line with the literature, the present study also found similar values regarding age, gender, LTOT, and NIV usage in patients with normonatremia and hyponatremia. CCI scores, leucocytes, neutrophils, AST, and CRP values were higher in hyponatremia whereas hemoglobin and lymphocytes were lower.…”
Section: Discussionsupporting
confidence: 92%
“…24 The classification of hyponatremia is reported as mostly mild and moderate. 13,24 In parallel to the literature, the rates of hyponatremia in home-manageable AECOPD was 22% in our study and most of these patients were classified as mild. Several parameters have been described to be related to hyponatremia.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Also, the data came from a single hospital and the results should not be generalized to other hospitals. Furthermore, other variable factors that may seem relevant to treatment failure, such as blood eosinophils, serum sodium, FEV1 <30% predicted, and treatment at discharge, were not obtained in this study [ 6 , 29 – 31 ].…”
Section: Discussionmentioning
confidence: 99%